Remittances, Dutch Disease, and Manufacturing Growth in Developing Economies. (10th July 2018) - Daway‐Ducanes, Sarah Lynne Salvador
Abstract: Remittances have grown tremendously in magnitude and economic importance in the past four decades, providing economies with additional disposable incomes and even serving as buffers against economic downturns. It is thus but fitting to ask how remittances have impacted on growth, particularly on manufacturing growth. This note presents a simple model linking remittances and manufacturing growth via a 'Dutch Disease' channel. Using Blundell and Bond's (1998) system general method of moments on a panel dataset of 56 developing economies from 1992 to 2016, we verify that remittances adversely affect manufacturing growth in economies that experience high real appreciation rates. This result is robust to alternate specifications, such as the inclusion of financial development indicators, the expansion of the sample to include high‐income economies, and the use of different sample periods.